Electron trapping and extraction kinetics on carrier diffusion in metal halide perovskite thin films. Issue 45 (25th September 2019) - Kang, Gyeongho; Yoon, Jun-Sik; Kim, Guan-Woo; Choi, Kyoungwon; Park, Taiho; Baek, Rock-Hyun; Lim, Jongchul
Abstract : An advanced transient optoelectronic method for time-resolved photoluminescence is developed; it is highly applicable and enables the accurate investigation of charge carrier diffusion in metal halide perovskite thin films. Abstract : Understanding initial electron distribution, diffusion, trapping and extraction processes for charge transfer kinetics in metal halide perovskite thin films is crucial for the improvement in device performances, but it still remains ambiguous in the research community. In particular, the kinetics of early-time carrier trapping should be considered with that of diffusion because these processes competitively occur in the same time domain. We herein presented the role of free electron trapping for the diffusion process by employing a dynamic trapping model on time-resolved photoluminescence, the most commonly employed technique to investigate charge transfer kinetics. The origin of the stretched exponential decay behavior of the trapping process, which appeared in the fast component of TRPL, was phenomenologically described and further clarified through a simulation study. We found that the electron injection coefficient at the interface between the perovskite and the electron transport layer was a more important determinant than the electron mobility of the perovskite in the electron extraction process.